2022
DOI: 10.1038/s41598-022-26243-6
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric assessment regarding craniocervical posture in orthodontic patients

Abstract: A major factor that contributes to dental malocclusions is represented by the positioning of the mandible. Considering the existing interconnections between the craniocervical and craniomandibular systems it is interesting to assess how changes in one system can influence the other, thus establishing a pattern in terms of certain cephalometric landmarks that orthodontists could consider when diagnosing and evaluating an orthodontic case. Therefore, the aim of this study was to investigate the connections betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Recently, the interrelation between malocclusion and craniocervical posture causes concerns in orthodontic field [ 23 , 26 , 32 , 48 ]. Numerous studies have shown significant correlations between craniocervical posture and craniofacial morphology [ 48 – 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, the interrelation between malocclusion and craniocervical posture causes concerns in orthodontic field [ 23 , 26 , 32 , 48 ]. Numerous studies have shown significant correlations between craniocervical posture and craniofacial morphology [ 48 – 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The teenage group's findings demonstrated that the craniofacial and craniocervical angle was negatively correlated with FMA. In contrast, the majority of recent investigations on the correlation between craniocervical posture and vertical skeletal pattern has suggested that patients with larger FMA typically have larger craniocervical angle [ 23 , 27 , 54 ]. A hypothesis was proposed that high angle adolescent patients with upper airway constriction will extend their entire cervical column instead of merely moving head forward to obtain enough airflow.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations